1999
DOI: 10.1021/tx980179f
|View full text |Cite
|
Sign up to set email alerts
|

C8-Arylguanine and C8-Aryladenine Formation in Calf Thymus DNA from Arenediazonium Ions

Abstract: Arylhydrazides, arylhydrazines, and N-alkyl-N-arylnitrosamines are metabolized to arenediazonium ions which yield C8-arylpurine adducts in calf thymus and cellular DNA. The mechanism of adduct formation has not been fully elucidated. C8-Arylguanine adducts likely form from direct aryl radical (Ar*) addition to the C8 position of guanine. However, the amounts of C8-aryladenine adducts measured here are inconsistent with direct radical attack at the C8 position of adenine. An intermediate product, an aryltriazen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 35 publications
4
53
0
Order By: Relevance
“…16 The addition of nucleotides to benzenediazonium ions, and the decomposition of these adducts to aryl radicals, has been reported. 41,42 Thus, in the absence of thiol, DNA itself may behave as a nucleophile toward 1 . The sequence of steps, e.g., protonation then addition, or addition followed by protonation, is not known, although the latter seems more likely given the electron-deficient nature of 1 .…”
Section: Discussionmentioning
confidence: 99%
“…16 The addition of nucleotides to benzenediazonium ions, and the decomposition of these adducts to aryl radicals, has been reported. 41,42 Thus, in the absence of thiol, DNA itself may behave as a nucleophile toward 1 . The sequence of steps, e.g., protonation then addition, or addition followed by protonation, is not known, although the latter seems more likely given the electron-deficient nature of 1 .…”
Section: Discussionmentioning
confidence: 99%
“…The C 8 -guanyl adducts, once formed, are stable to depurination, even in DNA (12). Interestingly, reaction of DNA with arene diazonium ions has recently been reported to cause extensive depurination (10), and N 7 -purine adducts have been considered intermediates.…”
Section: Discussionmentioning
confidence: 99%
“…(2) [8-13 C]Guo. [8][9][10][11][12][13] C]Gua (120 mg in 80 mL of 1 N HCl, 10 mM) was added to 400 mL of 0.20 M Tris base and the pH adjusted to 7.0, followed by the addition of 300 mg of ribose 1-phosphate and 9 mg of purine nucleoside phosphorylase (31). HPLC analysis (25) indicated that the reaction was >90% complete in 1 h (23°C).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context heterolytic dediazoniation has been reported to occur with methylbenzenediazonium and pnitrobenzenediazonium (pNO) ions in an aqueous medium (8,9), whilst other authors have interpreted their results as showing evidence of heterolytic and homolytic processes during the thermal and photochemical dediazoniation of several arenediazonium ions in trifluoroethanol and ethanol (10,11). Furthermore, in certain cases the reducing capacity of water has been sufficient to reduce arenediazonium to the aryl radical (12). It is obvious therefore that reaction conditions need to be chosen carefully when trying to establish the mechanisms involved in the decomposition of such versatile compounds as arenediazonium ions.…”
Section: Introductionmentioning
confidence: 99%